Analisis Perlakuan Verbal Bullying pada Remaja - Suri, Gusni Dian; Sari, Putri Melinda; Saidah, Nur; Tawalani, Yurike Adyel; Kichi, Annisa Yohana (Universitas Negeri Padang, 2022)
Cases of bullying are increasing day by day in Indonesia, which is not only done by adults but also teenagers and has an impact on teenagers. One type of bullying that is done by teenagers is verbal bullying. Verbal bullying is defined as an act of violence that is carried out verbally through words, such as insulting, mocking, or ridiculing. Many cases of bullying occur in teenagers. As a result of continuous bullying, it can affect self-confidence and mental health in adolescents who are victims of verbal bullying. This study aims to describe how the treatment of verbal bullying on adolescent victims of bullying. The method used in this study is a qualitative descriptive method. This study was conducted on 4 adolescent victims of bullying (1 boy, 3 girls; age 14-22 years; students and college students) through interviews. The data were analyzed using an interactive model consisting of three steps including data reduction, data presentation and drawing conclusions. The results showed that the treatment of verbal bullying on adolescents had positive and negative impacts, but the analysis showed that the negative impact was mostly caused by the treatment of bullying. On the positive impact it teaches children to be able to understand if they are in the position of victims of bullying so that they make children aware not to do that, mentally awaken children who are victims of verbal bullying to stay strong. While the negative impact is making children who are victims of verbal bullying become insecure, have psychological trauma because not all children can accept it. Based on this, parents, teachers and counselors work together to help and protect teenagers who are victims of bullying, giving teens the opportunity to understand what bullying is. For orders, it is necessary to enforce the law for bullying behavior so that bullying behavior is reduced and there is no more bullying so that teenagers become safe and comfortable without bullying. Teenagers are advised to consult with BK teachers in schools so that Guidance and Counseling services can be provided including information services, individual counseling services with a behavioral approach, group guidance services, classical services and mediation services to prevent violence in adolescents.